Happy birthday Willi Hennig!—Hyptia hennigi sp. nov. (Hymenoptera: Evaniidae), a fossil ensign wasp from Eocene Baltic amber - Jennings, John T.; Krogmann, Lars; Priya, Priya (Zootaxa, 2013)
The ensign wasp genus Hyptia Illiger was previously known from 52 extant New World species and one fossil species from Lower Miocene to Upper Oligocene Mexican amber. Hyptia hennigi sp. nov., from Eocene Baltic amber, is the oldest known species and the first member of the genus from the Old World.